A Survey of the Friends of the Library Recent Activities in Ohio: Report Description - McLean, Dulce DiDio; Ohio Library Association, Columbus ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1980)
In October 1978 a survey was conducted of Friends of the Library (FOL) activities during the preceding 6 years in support of public, branch, academic, public school, media center, institution, and special libraries in Ohio. The purpose of the survey was to identify and provide a comprehensive summary listing of the recent activities of Friends groups. A total of 315 libraries responded to the survey with 128 of them reporting FOL activities. Others reported interest in organizing or reactivating FOL groups. The type of FOL activities reported include fund raising and donation, acquisition of special collections and physical materials, sponsorship of programs, performance of services, fostering of professional growth, and development of community support for the library. A descriptive non-statistical analysis of the type of activities has been produced resulting in the publication of a separate directory of FOL activities in Ohio. The questionnaire and accompanying letter used for the 1978 survey are attached. (ESR)
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Community Involvement; Community Support; Financial Support; Library Acquisition; Library Surveys; Professional Development; Public Relations; Questionnaires; State Surveys; Volunteers; Friends of the Library; Library Support Groups -- Ohio; Tests/Questionnaires.; Reports, Descriptive